The epidemiology of bat rabies in New York State, 1988-92. - Childs, J. E. (Cambridge University Press, 1994)
In 1993 New York and Texas each reported a human rabies case traced to a rare variant of rabies virus found in an uncommon species of bat. This study examined the epidemiology of bat rabies in New York State. Demographic, species, and animal-contact information for bats submitted for rabies testing from 1988-92 was analysed. The prevalence of rabies in 6810 bats was 4.6%. Nearly 90% of the 308 rabid bats identified to species were the common big brown bat (Eptesicus fuscus), which comprised 62% of all submissions. Only 25 submissions were silver-haired bats (Lasionycterus noctivagans), the species associated with the two 1993 human cases of rabies, and only two of these bats were positive. Rabies was most prevalent in female bats, in bats submitted because of human [corrected] contact, and in animals tested during September and October. These results highlight the unusual circumstances surrounding the recent human rabies cases in the United States. A species of bat rarely encountered by humans, and contributing little to the total rabies cases in bats, has been implicated in the majority of the indigenously acquired human rabies cases in the United States. The factors contributing to the transmission of this rare rabies variant remain unclear.